UKURAN PERUSAHAAN DALAM MEMODERASI PENGARUH PROFITABILITAS DAN INTENSITAS MODAL TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN SUB SEKTOR BARANG PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2023 - Riyan Hidayat; Dini Martinda Lestari; Raden Irna Afriani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
The absence of taxes would threaten the government's efforts to maintain state revenues, which are strictly regulated to ensure stability. Without taxes, the government hardly to expanse the essential programs for society. This research examines the moderating of company size which profitability and capital intensity on tax avoidance in industrial goods sub-sector companies listed on the Indonesian Stock Exchange from 2019 to 2023. The method used quantitative research, uses secondary data from 40 companies. Used purposive sampling with 9 companies were selected as samples. Analysis conducted using multiple linear regression and Moderated Regression Analysis (MRA). The research shows a significance (sig) value for profitability 0.775, for capital intensity a sig value 0.001, for the interaction of profitability and company size a sig value 0.681, and for the interaction of capital intensity and company size a sig value 0.001.The results of the multiple linear regression analysis indicate that profitability does not effect tax avoidance, while capital intensity does influence tax avoidance. Moderated regression analysis using the MRA approach shows that company size strengthens the relationship between inventory intensity and tax avoidance. Furthermore, company size also strengthens the relationship between capital intensity and tax avoidance.